Prolonged atriocaval shunt utilization as a damage control tool for the management of juxtarenal IVC injury with a multitude of complex abdominal injuries - Jessica Potter; Stefan Leichtle; Edgar B Rodas; Mike Mallah; Kyle J Alexander; Sierra L Patterson; William B French; Levi Procter; Brian J Strife; Leopoldo Fernandez; Michel B Aboutanos (Trauma Surgery & Acute Care Open, 2025)
We describe the surgical dilemma of an adult male who arrived with a penetrating injury to the suprarenal inferior vena cava (IVC), where conventional intraoperative hemorrhage control failed. Our team innovated by using an atriocaval shunt for temporization of the injury during resuscitation, enabling us to return to the operating room and perform primary repair. Notably, the prolonged use of the atriocaval shunt as a damage control strategy represents a novel application, as it remained in place for several hours—a first in reported cases. We detail this technique, the multidisciplinary approach to managing concomitant severe injuries, and the resulting complications and outcomes. This case highlights the challenges of managing suprarenal IVC injuries and demonstrates the potential role of prolonged atriocaval shunting as a damage control strategy.